Eurocode 2 Design Data for Reinforced Concrete Columns - Tan, Kar Chun (Springer Nature Singapore : Imprint: Springer, 2019)
This book was written to facilitate column sizing and reinforcement design for structural engineers. It arranges the design data in a clearly structured manner, and provides quick and easy ways for engineers to compare the feasibility of multiple alternatives (various column sizes and reinforcement configurations). With the help of this book, engineers can rapidly produce outputs for architects, which the latter can incorporate into their architectural layout plans. These outputs can also benefit quantity surveyors, especially for costing purposes, and help avoid careless design errors. The book is chiefly intended for structural engineers who implement Eurocode 2 for reinforced concrete design. To gain the most from it, readers should possess a basic understanding of column design, e.g. the stresses and forces produced in columns and their reinforcements when subjected to axial load and bending moment. However, the book also provides explanatory notes for the design data tables, allowing them to be used without prior background knowledge.